Pengaruh Endorsement “Tasya Farasya Approved” Terhadap Brand Awareness Produk Somethinc Calm Down Cream (Survei Followers Instagram @tasyafarasya) - Wina Puspita Sari; Muria Putriana; Adi Budi Satrio; Djahwan Kamil; Indira Haniya Arasi; Muhamad Zidan Pahlevi; Muhammad Ihsan Darus; Syahwa Putri Ismaiga (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to determine the impact of the